2017
DOI: 10.1108/jhtt-09-2016-0052
|View full text |Cite
|
Sign up to set email alerts
|

Do travel decision-making styles and gender of generation Y have any association with travel information share on social networking sites?

Abstract: Purpose The purpose of this paper is to examine the association of gender and travel decision-making style of generation Y (Gen Y) – recreational, price conscious, impulsive, perfectionist, high quality, novelty seeker, habitual, confused by over-choice – to the use of social networking sites (SNS) for travel information share. The study focuses on purchase decision pattern of young travelers by examining the travel decision-making styles. Design/methodology/approach The author has adopted the quantitative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…They like to spend their time outside. In addition, the study of Choudhary and Gangotia (2017) suggested that this age group is frequently exposed to technology, which includes exploring travel information and making their own decisions. Because of the information that this group age is being aware of, according to Başarangil and Nişikli (2017), Gen Y also studied the effects of sustainable culture tourism perception on the intention to visit and weather to revisit.…”
Section: Resultsmentioning
confidence: 99%
“…They like to spend their time outside. In addition, the study of Choudhary and Gangotia (2017) suggested that this age group is frequently exposed to technology, which includes exploring travel information and making their own decisions. Because of the information that this group age is being aware of, according to Başarangil and Nişikli (2017), Gen Y also studied the effects of sustainable culture tourism perception on the intention to visit and weather to revisit.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the review of the literature revealed that Sproles and Kendall's (1986) original CSI measurement instrument has been applied in the travel context and modified accordingly (see, e.g., Choudhary and Gangotia, 2017). As suggested by Siu et al (2001), a reliable and valid instrument is required for consumer profiling.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it can be argued that these consumers will prefer different, renovated and likely rejuvenated cultural heritage sites, and they will be their first visitors. It should also be noted that the study conducted by Choudhary and Gangotia (2017) shows that young adults are novelty-conscious travellers who seek and prefer new destinations. Recreational, hedonistic shopping consciousness is a fourth CDMS proposed by Sproles and Kendall (1986).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Big data analytics could be used to help improve the frontline employee service offerings (Motamarri et al , 2017). Big data analytics provides a bigger view of a message strategy, customer’s satisfaction and customer complaints through social media exchanges (Choudhary and Gangotia, 2017; Kizildag et al , 2017; Leung et al , 2017a, 2017b; Park et al , 2016). This information enables the organizations to offer amenable solutions to enhance customer value (Wilder et al , 2014).…”
Section: Methodsmentioning
confidence: 99%